The IL23R Arg381Gln non-synonymous polymorphism confers susceptibility to ankylosing spondylitis. Issue 10 (16th January 2008) - Rueda, B; Orozco, G; Raya, E; Fernandez-Sueiro, J L; Mulero, J; Blanco, F J; Vilches, C; González-Gay, M A; Martin, J
Abstract : Objectives: Recent results have shown that the IL23R gene, coding for a subunit of the interleukin-23 receptor, is strongly associated with autoimmunity. The aim of the current study was to investigate, for the first time, the possible involvement of the IL23R gene in genetic susceptibility to ankylosing spondylitis (AS). Methods: We carried out a case–control association study in which 365 patients with AS and 500 blood bank donors were included. Eight single nucleotide polymorphisms (SNPs) spanning the IL23R gene were selected as genetic markers for our association study and were genotyped using a Taqman 5′ allelic discrimination assay. Results: Interestingly, we observed association of two of eight IL23R genotyped SNPs. The strongest effect was conferred by the non-synonymous rs11209026 (Arg381Gln) SNP (odds ratio 0.46 95% confidence interval 0.2 to 0.7 p = 0.001). Similarly, the IL23R rs1343151 SNP showed association with AS genetic susceptibility (odds ratio 0.68 95% confidence interval 0.55 to 0.83 p = 0.0002). After a conditional case–control test we observed that the effect of these two genetic variants was independent of linkage disequilibrium. Conclusions: These results suggest that the IL23R gene seems to be involved in AS genetic predisposition.